Evaluation of building materials using infrared thermography - Eva Barreira (2007)
Infrared thermography is a non-destructive testing technology that can be applied to determine the superficial temperature of objects. In this method, detectors collect infrared radiation to create a thermal image showing the superficial temperature distribution. Despite thermography's many potentials, its application to building materials has not been greatly studied yet. The parameters that may affect measurements are not completely understood and interpreting the results becomes difficult and confusing. To assess the use of thermography, some simple experiments were carried out at the Building Physics Laboratory (LFC) of the Engineering Faculty of Porto University (FEUP). A sensibility study was performed with LFC's equipment to evaluate how measurements are influenced by emissivity, environmental conditions, colour and reflectivity. The wetting and drying process of building materials was also studied, as water evaporation is an endothermic reaction inducing local surface cooling. And, lastly, the comfort of some interior floor coatings was evaluated by comparing thermal images obtained from the sole of a barefoot after having been in contact with different materials. The results of these experiments are presented in this paper.